Stress in novice nurses in new work environments: a systematic review - Narbona-Gálvez, Ángela; García-Iglesias, Juan Jesús; Ayuso-Murillo, Diego; Fontán-Vinagre, Guadalupe; Gómez-Salgado, Juan; Allande-Cussó, Regina; Fagundo-Rivera, Javier; Macías-Toronjo, Israel; Ruiz-Frutos, Carlos (Frontiers in Public Health, 2024)
BackgroundInexperienced nursing care can compromise the quality of care and the well-being of patients. The aim of this study was to assess the main sources of stress encountered by nurses and novice nurses in a setting not previously experienced.MethodsA systematic review was conducted following the PRISMA format in Pubmed, Scopus, Web of Science, and CINAHL electronic databases in March 2024. A total of 395 studies were identified, of which 16 met the inclusion criteria. Selection was made on the basis of topic relevance and methodological quality, assessed using the critical tools of the Joanna Briggs Institute (JBI).ResultsA total of 16 studies were included in this review. Of the 16 selected, 10 were cross-sectional studies, 3 were cohort studies, 2 were qualitative, and 1 was a systematic review. The studies revealed that the main stressors for novice nurses included time management, workload, and interpersonal relationships. The results underline that organizational factors, such as lack of support and high work demands, play a key role in generating stress.ConclusionIdentifying and addressing the key challenges faced by novice nurses, such as workload, adjustment to the environment, professional expectations, and interpersonal relationships, is crucial to sustain their professional engagement and ensure the quality of health care. This understanding is essential for creating efficient policies and practices that enhance the occupational well-being and stability of nurses in the workforce.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024520651, CRD42024520651.